Combination of 3D Printing and Electrospinning Techniques for Biofabrication. Issue 7 (9th January 2022) - Yang, Dan‐Lei; Faraz, Fazal; Wang, Jie‐Xin; Radacsi, Norbert
Abstract: This review presents the different combination methods of 3D printing and electrospinning processes and discusses the advantages of each method. Also, the applications of products of the hybrid process in the biomedical field, including tissue engineering and regenerative medicine, are thoroughly discussed. 3D printing and electrospinning are separate approaches for generating structured materials in a variety of biomedical applications. However, some shortfalls, such as the low resolution of 3D printing and uncontrollable shape of electrospun products, limits their application performances. Therefore, new ideas that combine 3D printing and electrospinning methods are proposed to give full play to their strengths and mitigate their weaknesses, which provide an effective and powerful platform for fabricating novel structural materials. Finally, a future vision regarding challenges and perspectives in the combination of 3D printing and electrospinning techniques is proposed. Abstract : Combining 3D printing and electrospinning techniques shows tremendous potential in biofabrication. Scaffolds or implants for repairing tissues and organs with very different structures can be created in a bionic style taking the furthest advantage of each technique, which cannot be achieved by other biofabrication methods. The optimization of hardware facilitates the integration of 3D printing and electrospinning setups in a compact and automatized platform.